2012
DOI: 10.1002/jso.23066
|View full text |Cite
|
Sign up to set email alerts
|

Does non‐curative gastrectomy improve survival in patients with metastatic gastric cancer?

Abstract: Non-curative gastrectomy does not improve survival in patients with metastatic gastric cancer, nor reduces the rate of late occlusions. There is no need for prophylactic palliative gastrectomy in patients with gastric cancer who do not have bleeding or obstruction preoperatively. Among those patients, postoperative chemotherapy seems to improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Both positive and negative findings have been noted in retrospective studies [513]. However, none of the studies analyzed the survival benefit of palliative gastrectomy in subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both positive and negative findings have been noted in retrospective studies [513]. However, none of the studies analyzed the survival benefit of palliative gastrectomy in subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies found a protective role for palliative gastrectomy in overall survival of patients with metastatic gastric cancer [510], others did not [1113]. The major issue underlying the controversy is that none of the studies was prospectively and randomly designed.…”
Section: Introductionmentioning
confidence: 99%
“…Median overall survival durations of 8.5-13.8 months have been reported following resectional surgery alone as the principal treatment modality for patients with incurable gastric cancer, 18,25,[53][54][55][56][57] compared with a median overall survival of 13.8 months for patients HER2-positive tumours who received trastuzumab in the TOGA trial. 49 The comparable survival demonstrated for these treatment modalities suggests that an individualized, patient-centred multidisciplinary approach should be advocated, offering either operative or nonoperative treatment after careful risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the value of palliative gastric resection come largely from retrospective series without real consensus regarding survival advantage. 20,21 However, a generalized consensus exists that a palliative resection can be recommended only for patients of reasonable physical condition, where metastatic disease is limited in extent, or where warranted by symptoms. Patients with advanced disease are often malnourished and have less physiological reserve, and the potential benefit of palliative resection needs to be balanced against the heightened surgical risks and the effect on quality of life.…”
Section: Commentmentioning
confidence: 99%